2018
DOI: 10.1002/icd.2117
|View full text |Cite
|
Sign up to set email alerts
|

Differences in sensory responses among children with autism spectrum disorder and typical development: Links to joint attention and social competence

Abstract: The current study investigated relations among children's sensory responses, dyadic orienting, joint attention, and their subsequent social competence with peers. Participants were 38 children (18 children with autism spectrum disorder [ASD] and 20 developmentally matched children with typical development) between the ages of 2.75 and 6.5 years. Observational coding was conducted to assess children's joint attention and dyadic orienting in a structured social communication task. Children's sensory responses an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 59 publications
0
7
0
1
Order By: Relevance
“…Moreover, domain general processes such as ocular motor control (271), sex differences (272), or predictive processing (213) may moderate the development of social attention symptoms development in ASD. Atypical sensory processing may also influence social attention development (273)(274)(275). However, joint attention may also predict the second-year sensory regulation in infants at risk for ASD (276).…”
Section: Social and Non-social Attention Developmentmentioning
confidence: 99%
“…Moreover, domain general processes such as ocular motor control (271), sex differences (272), or predictive processing (213) may moderate the development of social attention symptoms development in ASD. Atypical sensory processing may also influence social attention development (273)(274)(275). However, joint attention may also predict the second-year sensory regulation in infants at risk for ASD (276).…”
Section: Social and Non-social Attention Developmentmentioning
confidence: 99%
“…Groups did not significantly differ in household income, t (31) = 0.645, p = 0.52, d = 0.47; mother’s ethnicity, χ 2 (4, N = 38) = 6.05, p = 0.20; or father’s ethnicity, χ 2 (4, N = 36) = 5.63, p = 0.23. Finally, as group differences in children’s effortful control (ASD < TD), executive function (ASD < TD), emotion regulation (ASD < TD), and joint attention (ASD < TD) have been reported in our prior work (Dakopolos & Jahromi, 2018; Jahromi et al, 2013), these were not reported as part of the present study.…”
Section: Resultsmentioning
confidence: 76%
“…Based on these findings, Molenhuis et al (2016) concluded that Cntn4-deficiency does not affect ASD-specific phenotypes, but rather results in subtle non-ASD-specific changes in responsiveness to stimuli and cognitive performance. Notably, hyper-responsiveness to acoustic stimuli is a phenotype that has been associated with ASD and other neuropsychiatric disorders ( Baranek et al, 2013 ; Green et al, 2013 ; Acevedo et al, 2018 ; Dakopolos and Jahromi, 2019 ; Hornix et al, 2019 ).…”
Section: Neurophysiological Roles Of Chl1 Cntn6 mentioning
confidence: 99%